Comparison between Early and Late Nasolacrimal Stent for Congenital Nasolacrimal Obstruction - Jamshaid Hameed, Mohammad Moin, Asif Mahmood Khokhar (Pakistan Journal of Ophthalmology, 2018)
Purpose: To compare success of silicone intubation through the nasolacrimal pathway for treatment of congenital nasolacrimal obstruction in children between the age 1 – 3 years and 3 – 5 years in case of failed probing. Study Design: Quasi experimental study. Place and Duration of Study: In Mayo hospital and Lahore General Hospital during the period of 2007 to 2016. Material and Methods: It is a retrospective review of 98 children with epiphora due to congenital nasolacrimal obstruction. The patients underwent probing and the cases in whom probing was failed were planned for silastic intubation. We divided them into 2 age groups. In group I children had age between 1 – 3 years and 46 patients were included in this group. In group II children had age between 3 – 5 years and 52 patients were included in this group. In Mayo hospital and Lahore General Hospital during the period of 2007 to 2016. Results: The success rate in group I (with younger children) was 91% while in group II (with older children) success rate was 82%. Conclusion: Our study shows that nasolacrimal stent implantation is better option in children with persistent epiphora after probing between 1-3 years. Keywords: Epiphora, nasolacrimal stent, congenital nasolacrimal obstruction, silastic nasolacrimal intubation.